THE METHODOLOGICAL DILEMMA REVISITED : Creative, Critical and Collaborative Approaches to Qualitative Research for a New Era - Gallagher, Kathleen, 1965 Dec. 31-, editor 201562 (London ; New York : Routledge, Taylor & Francis Group, 2018)
Includes bibliographical references